Tracing Secularism: Religion, Power, and Violence in Western and Eastern (Islamic) World - Muhammad Rizkita; Abdy Nur Muhammad; Alniatul Fadilah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study examines the complex relationship between religion, violence, and secularism by analyzing the perspectives of thinkers such as Marx, Nietzsche, Hobbes, and Karen Armstrong. Although religion is often considered the primary source of violence, this paper argues that violence related to religion is better understood as a manifestation of deeper political, economic, and existential forces. This study also explores the different paths of secularism development in the Western and Islamic worlds. In the West, secularism emerged as a revolutionary response to the corruption of church authority during the Dark Ages. On the other hand, secularism in the Islamic context was shaped by the need to manage religious diversity, as illustrated by the Medina Charter. The method used in this research is a qualitative-historical analysis of texts discussing the relationship between religion, violence, and the state. The novelty of this research lies in the application of José Casanova's concept of secularism to reveal that, despite the process of secularization, the West has experienced a resurgence of religion in the public sphere—thus demonstrating the failure of secularism as an ideology and nor statecraft principles.